2019
DOI: 10.1108/afr-05-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

The role of savings mobilization on access to credit: a case study of smallholder farmers in Ghana

Abstract: Purpose The purpose of this paper is to examine the effect of savings mobilization on access to credit among smallholder farmers’ in the Birim central municipality of Ghana. Design/methodology/approach A cross-sectional primary data set was used to estimate the factors influencing smallholder farmers’ access to credit and size of loan to be borrowed using the IV-Probit and IV-Tobit model. Findings The results of the study revealed that savings mobilization has a positive significant impact on access to cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Therefore, this can result in the loss of earnings for the lender who decides not to grant the loan. Our result bears rich parallels to those of Abdallah [31] and Twumasi et al [51], who found that transaction costs such as transport costs decrease the likelihood of farmer AC in SSA and Ghana, respectively.…”
Section: Determinants Of Acsupporting
confidence: 87%
See 4 more Smart Citations
“…Therefore, this can result in the loss of earnings for the lender who decides not to grant the loan. Our result bears rich parallels to those of Abdallah [31] and Twumasi et al [51], who found that transaction costs such as transport costs decrease the likelihood of farmer AC in SSA and Ghana, respectively.…”
Section: Determinants Of Acsupporting
confidence: 87%
“…Undeniably, the high level of education is important human capital, which could enable farmers to accurately understand credit requirements compared to their counterparts with a lower educational level. Similar observations have been made by Twumasi et al [51] and Ouattara et al [13], who found that the excellent level of education is one of the key determinants of farmers' access to credit, respectively in Ghana and Côte d'Ivoire.…”
Section: Determinants Of Acsupporting
confidence: 85%
See 3 more Smart Citations